The Influence Of Work Environment And Public Participation On The Performance Of Employees Of The Population And Civil Registration Service Of Gowa Regency - Nusul Fikran; Sitti Nurbaya; Zalkha Soraya (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to determine the influence of the work environment and community participation on the performance of employees at the Department of Population and Civil Registration of Gowa Regency. This research uses a quantitative descriptive approach. Data were collected through questionnaires distributed to 54 respondents who are employees of the department. Data analysis techniques include descriptive analysis, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results show that partially, both work environment and community participation variables have a positive and significant effect on employee performance. However, simultaneously, the work environment and community participation do not have a significant effect on the performance of employees at the Department of Population and Civil Registration of Gowa Regency.